Enterprise-Grade IT Security for Small and Medium Businesses Building Security Systems, in Plain English - Cherry, Denny (Apress L. P., 2022)
Understand the IT security features that are needed to secure the IT infrastructure of a small to medium-size business. This book will give IT managers and executives a solid understanding of the different technology solutions that their business relies upon-or should be employing-in order to make reasoned decisions regarding the implementation of those features. Coverage includes multi-factor authentication, firewalls, zero-trust environments, network segmentation, remote access solutions, and the people aspects of security that are often overlooked and represent an organization's biggest vulnerability. Chapters on the various technologies such as multi-factor authentication and zero-trust environments explain in plain English the values and benefits that each technology provides. Clear technical explanations are accompanied by business case explanations that explain the "why" of each technology and when each technology should be implemented. You will come away equipped to have business-driven discussions with your IT staff that allow for a productive balancing of the need for security with the need to do business and drive profits.